2004
DOI: 10.1046/j.1439-0418.2003.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Apple and peach fruit volatiles and the apple constituent butyl hexanoate attract female oriental fruit moth, Cydia molesta, in the laboratory

Abstract: Volatiles emitted from immature and mature peach and apple fruits were all attractive to mated female oriental fruit moth, Cydia molesta (Busck), in a dual choice arena. Females did not discriminate between odours emitted by these two major host plants. The same natural blends were behaviourally ineffective for virgin females. A major component of apple fruit volatiles, butyl hexanoate, also attracted female C. molesta. Mated females were attracted to two medium dosages, while virgin females responded positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 22 publications
0
55
0
Order By: Relevance
“…This demonstrates that pheromone and plant volatile processing is not completely separate in the AL of G. molesta. The high percentage of AL neurons responding to 5VB underlines its importance in guiding host-finding behaviour not only in females (Natale et al, 2004;Piñero and Dorn, 2007), but also in males (N.V., personal observation). Fewer neurons responding to PE might be due to the fact that pears are only a secondary host plant for G. molesta, unlike its related species C. pomonella (Knight et al, 2005).…”
Section: Odour Quality Codingmentioning
confidence: 97%
See 1 more Smart Citation
“…This demonstrates that pheromone and plant volatile processing is not completely separate in the AL of G. molesta. The high percentage of AL neurons responding to 5VB underlines its importance in guiding host-finding behaviour not only in females (Natale et al, 2004;Piñero and Dorn, 2007), but also in males (N.V., personal observation). Fewer neurons responding to PE might be due to the fact that pears are only a secondary host plant for G. molesta, unlike its related species C. pomonella (Knight et al, 2005).…”
Section: Odour Quality Codingmentioning
confidence: 97%
“…Also, attraction towards a blend of five plant volatiles ((Z)-3-hexenyl acetate, (Z)-3-hexenol, (E)-2-hexenal, benzaldehyde and benzonitrile) has been recently reported in G. molesta females (e.g. Natale et al, 2004;Piñero and Dorn, 2007;Piñero et al, 2008). The response of G. molesta to ethyl (E,Z)-2,4-decadienoate (pearester: PE), a volatile emitted by ripe pears (Knight and Light, 2004), has also been observed in some apple orchards (F. M. Molinari, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…The European corn borer Ostrinia nubilalis (Lepidoptera: Pyralidae) successfully added maize to its original host range in spite of the toxic properties of hydroxamic acids from this plant, in particular 2,4-dihydroxy-7-methoxy-l,4-benzoxazin-3-one (DIMBOA) (Campos et al, 1988;Martel et al, 2003). Likewise, apple was initially reported only as a secondary, relatively unimportant host plant of the oriental fruit moth (Rothschild and Vickers, 1991), but its significance as a host is continuously increasing (Natale et al, 2004;Myers et al, 2006), indicating the potential of this insect to rapidly adapt to new hosts. Our results suggest that in future, G. molesta could include juglandacean plants into its host range, provided other factors are favorable.…”
Section: Discussionmentioning
confidence: 99%
“…Natale et al (2003) reported that excised peach shoots were attractive to mated OFM females, and identified mixtures of (Z)-3-hexenyl acetate, (Z)-3-hexenol and benzaldehyde as OFM female attractants from the excised plants under laboratory conditions. They also reported that the major component of apple fruit volatiles, butyl hexanoate, was also attractive for mated OFM females (Natale et al 2004). We also found that newly planted peach trees are especially attractive to mated OFM females for oviposition.…”
Section: Introductionmentioning
confidence: 98%